Tecnologias e gestão educacional no contexto pandêmico: a experiência de Três Passos/RS - Schweigert, Dione Noschang (2023)
This research project is linked to LP1 (Educational Policies and Management) of the Professional Master's Program in Public Policies and Educational Management at the Federal University of Santa Maria (UFSM) and to the Study Group on Education, Technologies, and Society - INTERFACES/CNPq. It addresses the themes of Educational Management and Educational Technologies, focusing on the experience of the municipality of Três Passos in the pandemic context. The general objective is to understand how educational management and the municipal government of Três Passos – RS articulated technological strategies to ensure the right to learning as outlined in the National Common Curricular Base (BNCC), during the period of remote learning and the return to in-person education. As a methodology, a case study was employed, using semi-structured interviews with four managers working in the Municipal Education Network, in addition to literature review and document analysis to gather data. For data analysis, the Textual Discursive Analysis (ATD) proposed by Moraes and Galiazzi (2007) was adopted, generating four categories: Integration of technological resources in education: a look at the objectives of the BNCC during the pandemic; Transforming teaching in times of crisis: actions of the municipal network during the pandemic for the use of educational technologies; Challenges and opportunities in education in times of pandemic: adaptation of teachers and managers to new ways of teaching and learning; An analysis of municipal public policies and alignment with SDG 4 in Três Passos. Therefore, the dissertation addressed the intersection between educational management, educational technologies, and the need to ensure equity in education, especially in a challenging context like the pandemic. The analysis of the actions of the municipal administration of Três Passos demonstrated the resilience and adaptability of managers and teachers in the face of the transformations imposed by remote learning. Furthermore, the research indicated the alignment of municipal policies with the principles of the 2030 Agenda, emphasizing the need to expand knowledge about the Sustainable Development Goals (SDGs). As an educational product, a Massive Open Online Course (MOOC) is proposed for managers to promote the inclusion of educational technologies in schools through an understanding of the goals of the 2030 Agenda. The proposal represents a significant step towards the training of managers and the promotion of a more inclusive and sustainable education. It is evident that, in addressing the challenges of education in the 21st century, innovation and the integration of technologies play a fundamental role, aligning with the vision of a fairer and more inclusive society proposed by the 2030 Agenda.